Gulf Pidgin Arabic: An Empirical Investigation into its Emergence and Social Attitude - ABED, LOWAI GHAZI (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2017)
While there are many contact languages that have been covered by sociolinguistic research, to date, most of those documented contact varieties are European-based and many have emerged out of imperial forces driven by the European colonial expansion around the world and subsequently an active slave trade between the sixteenth and eighteenth centuries. However, there are contact varieties that have come about without any European influence, but rather through recent international migration and economic integration generated by globalisation. This is potentially the case for the variety that has been defined as Gulf Pidgin Arabic (GPA) in Saudi Arabia and the countries of the Gulf Cooperation Council, the (GCC) states. This region has witnessed a rapid economic development since the early 1960s and 1970s generated by the oil industry. Hence, the region subsequently witnessed a large influx of unskilled/semi-skilled migrant labourers mainly from the Indian subcontinent and South East Asia. However, due to the indentured labour environment that this specific migrant community has to endure, GPA has emerged as a communication tool between the local Gulf nationals in the region and the unskilled/semi-skilled migrant labourers. This pidgin variety received little attention from the field of pidgin and creole studies. The rationale behind this research is primarily to bring a more globalised view on the study of contact languages by introducing GPA to the field and exploring it from a sociolinguistic point of view rather than solely linguistic. To carry out this research, a mixed method research design was applied, where both qualitative and quantitative methodologies were used to examine data drawn from two distinct sources. These include a one to one semi-structured interviews and an online survey questionnaire. Thus, an extensive sociolinguistic study was undertaken in order to understand the social circumstances which have resulted in the development of GPA. In addition, the social attitude towards this language was also evaluated from the perspective of its speakers. Findings from the interviews conducted with the former disclosed that their lives primarily focused on labour-related pursuits, while exposure to the local culture within their host social environment was curtailed and restricted. In addition, GPA was found to be mainly used to communicate in work situations. Finally, data collected from the questionnaire has shown that a neutral attitude was held by the local population towards unskilled/semi-skilled migrant workers. However, respondents expressed a preference for residential segregation. In addition, the questionnaire highlighted their negative attitude toward GPA, especially in relation to its usage and spread. In summary, the conclusions drawn from this research have demonstrated that the context and social atmosphere in which GPA is spoken overlap with other contact languages that have been developed in many locations throughout the world. Based on the results of this study, the theoretical, practical and social implications of GPA are provided, as well as predictions on the future of GPA.
APPROVED